The formation of islamic character through the student-led conference (SLC) program (in grade 9 smp insan cendekia madani boarding school development Serpong, South Tangerang City) - Chabib Mustofa; Syahidah Rena; M. Ubaidillah Al-Ghifary (Goodwood Publishing, 2025)
Purpose: This study aims to examine the implementation of the Student-Led Conference (SLC) program for grade 9 students at SMP Insan Cendekia Madani BSD, Ciater Village, Serpong District, South Tangerang City, analyze its role in developing Islamic character, and identify supporting and inhibiting factors.Research methodology: The research employs a descriptive-qualitative approach, with data collected through observation, documentation, interviews with relevant stakeholders, and triangulation to ensure data validity. Results: The findings reveal that the SLC program, implemented through structured stages, effectively fosters Islamic character traits such as independence and responsibility among students. Supporting factors include strong commitment and collaboration from the school, parents, and students. Inhibiting factors include parents’ delays or absence during scheduled SLC sessions, difficulties in understanding students’ presentations, and overlapping school programs requiring simultaneous completion by teachers. Conclusions: The SLC program serves as an innovative strategy for character education, particularly in enhancing students’ independence and responsibility in line with Islamic values. Successful implementation depends on consistent parental involvement, clear communication, and effective time management at the school level. Limitations: The study is context-specific, focusing solely on grade 9 students at SMP ICM BSD, and may not fully represent other institutions or grade levels. Contribution: This research provides empirical insights into integrating SLC into Islamic character education, offering practical recommendations for educators to optimize parental engagement and manage program scheduling effectively